PENGAPLIKASIAN DIGITAL MARKETING TOOLS TERHADAP QBEE NAIL SALON - Anthoni Sentoso; Angeline; Angela Adriyanti Yang; Dennis Yang; Leonard Suryadi Yusuftan; Whitney Ong (Jurnal Cakrawala Ilmiah, 2023)
Research on the application of digital marketing tools was conducted at Qbee Nail Salon, which is located in Batam City, with the aim of helping MSMEs in increasing their audience to profit. A descriptive research method was used with the collection of primary and secondary data sources. The results are in the form of application of tools such as Whatsapp Business, Mailchimp, Instagram to Linktree. As for suggestions that can be given in the form of further learning about the tools that have been implemented, put them to good use and use them consistently, in order to maintain and increase the performance level of Qbee Nail Salon's branding.